Completeness and Appropriateness of Integrated Management of Neonatal & Childhood Illness (IMNCI) Forms Filled By the Interns in Field Area of Tertiary Care Hospital in Gujarat - Rujul P Shukla; Neha Das; Dinesh Kumar; UdayShankar Singh (Medsci Publications, 2018)
Background: IMNCI is an important strategy being implemented across our country with aim to reduce infant & under-five mortality. Training of MBBS students in IMNCI is being carried out at PramukhSwami Medical College, Karamsad since more than 10 years. In this study, quality of IMNCI forms filled by interns during their posting at Urban Health Training Centre in terms of completeness & appropriateness had been studied. Objectives: To assess & compare completeness & appropriateness of 2 months upto 5 years IMNCI forms of interns of 2012-13 & 2013-14 MBBS batch. Methodology: This was a record based study in which analysis of filled forms of 2 MBBS batches was done. Completeness criterion was based on completely filled forms & appropriateness criterion was based on criterion of completely filled correct forms. Results: All available 238 forms were analyzed. Completeness was found in 8.3% (n=10) & 10.3% (n=12) forms of 2012-13 & 2013-14 batch respectively. Appropriateness of forms was 8.3% (n=10) forms of 2012-13 batch & 8.5% (n=10) forms of 2013-14 batch. Completeness & appropriateness was found to be of poor quality in both the batches. Conclusion: Repeat training is essential in internship as completeness & appropriateness of the forms was found to be poor in the study.